Effects of Conflict between Pastoralist and Crop Farming Communities on Households’ Food Security in Kwara State, Nigeria - SALAU, Shehu Abdulganiyu; AYANDA, Ibrahim Folorunsho; NOFIU, Nofiu Babatunde (Journal of Agriculture and Environmental Sciences, 2020)
Pastoralists-farmers’ conflicts in Nigeria have grown, spread and intensified over the past decade and today pose a threat to national survival. Thus, this study measured food security status, assessed the effect of pastoralist- crop farmers’ conflict on food security and described the coping strategies employed by the respondents to reduce the effects of the conflict. Proportional sampling method was used to select a sample of 200 farming households. The analytical tools include descriptive statistics, logistic regression and food security index. The study indicated that 54.5% and 45.5% of the respondents were food secure and food insecure, respectively. Furthermore, pastoralist-crop farmers’ conflict, household size, sex, farm distance and access to co-operatives were the significant factors driving to food security in the area. Moreover, farmers generally used a combination of strategies to manage conflict. The ‘use of job experience, hard-working, early cropping, appease other party and seeking for help from relatives, village leaders and governments were some of the effective coping strategies used by the respondents to reduce the effects of conflict. Consequently, ranching and use of Rural Grazing Area (RUGA) settlement be encouraged by the government to reduce the effect of the conflict. Policies and strategies aimed at reducing the household size and enhancing cooperative formation should be pursued